(untitled) (GEOMATE Journal, 2023)
In recent years, it has been considered to secure water and food using seawater desalination technology, and a new simple desalination material for reducing the high concentration of sodium chloride in seawater is required. In this study, desalting agents were prepared from natural zeolite, obtained from Kagoshima prefecture, Japan, with the addition of calcined Ca-Fe type layered double hydroxide (LDH), to desalinate seawater for cultivation. By treating with the mixture of natural zeolite and calcined Ca-Fe LDH at a mixing ratio of 5: 4, the salinity could be reduced from 3.61% in seawater to 0.97% by cation exchange reaction of natural zeolite and reconstruction reaction of calcined Ca-Fe LDH, and the pH of the obtained solution is 8.4-9.0. The desalination reaction using this mixture was almost the same regardless of temperature. Radish sprouts, bean sprouts, and mung beans could be harvested using seawater treated with a mixture of natural zeolite and calcined Ca-Fe LDH, while it was not possible to harvest using seawater.